VEGF mediated signaling in oral cancer - Lin, X.; Khalid, S.; Qureshi, M. Z.; Attar, R.; Yaylim, I.; Ucak, I.; Yaqub, A.; Fayyaz, S.; Farooqi, A. A.; Ismail, M. (Cellular and Molecular Biology, 2016)
Increasingly it is being realized that oral cancer arises from genetic/epigenetic mutations, dysregulations of spatio-temporally controlled signal transduction cascades and loss of apoptosis. Epidemiological studies have provided a stronger association between tobacco use (chewed and smoked) and oral cancer. Nevertheless, alcohol has also gained attention as a significant risk factor, having a multiplicative synergistic cancer promoting effect with tobacco. Vascular Endothelial Growth Factor (VEGF) mediated signaling has gained limelight because of its instrumental role in endothelial cell proliferation, survival, invasion, migration, chemotaxis of bone marrow (BM)-derived progenitor cells, vasodilation and vascular permeability. In this review we provide most recent updates on involvement of VEGF/VEGFR signaling axis in oral cancer. We partition this multi-component review into different sections and summarize latest advancements related to therapies against VEGF/VEGFR signaling axis and how microRNAs tactfully modulate VEGF and VEGFR in oral cancers. Data obtained through preclinical and clinical studies has revealed that therapeutic benefits associated with VEGF-targeted therapy are complicated in different cancers and involve myriad of mechanisms. A better understanding of VEGF/VEGFR mediated signaling in oral cancers and testing of novel therapeutic agents in preclinical models will prove to be helpful in effective translation of safest drugs from benchtop to the bedside.